2008
DOI: 10.1007/s11055-008-0021-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term consequences of prenatal exposure to lead on brain development in rats

Abstract: Administration of singe doses of lead citrate (200 mg/kg) to pregnant rats (on day 18 of pregnancy) was followed by the appearance of destructive changes in brains at age 40 days, with cysts, foci of gliocyte proliferation, pyknotic neurons, and decreases in NADH and NADPH diaphorase activities in neocortical and hippocampal neurons. Decreases in the density of neurons in the cortex and decreases in cortical thickness were also observed. The intensity of free-radical oxidation in the cortex increased three-fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Dietary patterns identified via PCA were predictive of bone and B-Pb in elderly men in the United States and Sweden, and in Korean adolescents and adults (18–20). To our knowledge, dietary pattern analysis has not been undertaken for pregnant women in association with biomarkers of lead exposure: this is important because the fetus is vulnerable to the effects of lead due to the rapid development of the nervous system (21, 22). During pregnancy, lead crosses the placenta freely (23, 24) and can adversely affect a range of birth outcomes, with the potential for lifelong impact on the growth and development of the child (21).…”
Section: Introductionmentioning
confidence: 99%
“…Dietary patterns identified via PCA were predictive of bone and B-Pb in elderly men in the United States and Sweden, and in Korean adolescents and adults (18–20). To our knowledge, dietary pattern analysis has not been undertaken for pregnant women in association with biomarkers of lead exposure: this is important because the fetus is vulnerable to the effects of lead due to the rapid development of the nervous system (21, 22). During pregnancy, lead crosses the placenta freely (23, 24) and can adversely affect a range of birth outcomes, with the potential for lifelong impact on the growth and development of the child (21).…”
Section: Introductionmentioning
confidence: 99%
“…Because lead is transferred freely across the placenta (the ratio of fetal:maternal blood lead is about 0.7–0.9 ( Rudge et al, 2009 , Schell et al, 2003 )) and across the blood–brain barrier, in utero exposure to lead may contribute to adverse cognitive outcomes: experimental animal studies suggest that the fetus is particularly vulnerable to the effects of lead because of effects on processes critical to the development of the central nervous system ( Basha and Reddy, 2015 , Ryzhavskii et al, 2008 ). Thus, relatively low levels of exposure that do not greatly harm the mother may have a profound effect on the development of the fetus, and on subsequent development and behaviour during childhood.…”
Section: Introductionmentioning
confidence: 99%
“…Pb exposure during pregnancy is associated with a variety of neonatal perturbations, including low birth weight, delayed development and maturation, as well as later developing behavioural outcomes (Chang et al, 2012 ). Experimental studies demonstrated that administration of Pb to pregnant rats produced destructive changes in the brains of their offspring (Lebed'ko & Ryzhavskii, 2005 ; Ryzhavskii et al, 2008 ). Differential gender effects were also observed after in utero exposure to Pb throughout full gestation (Cory-slechta et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%